2020
DOI: 10.3390/cells9061502
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Xenopus Oocyte Meiosis: Toward the Genomic Era

Abstract: The study of oocytes has made enormous contributions to the understanding of the G2/M transition. The complementarity of investigations carried out on various model organisms has led to the identification of the M-phase promoting factor (MPF) and to unravel the basis of cell cycle regulation. Thanks to the power of biochemical approaches offered by frog oocytes, this model has allowed to identify the core signaling components involved in the regulation of M-phase. A central emerging layer of regulation of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 133 publications
(235 reference statements)
1
20
0
Order By: Relevance
“…In understanding the susceptibility of oocytes to changes in proteostasis, it is important to note that transcription ceases when oocytes complete their growth phase prior to reentry into meiosis (Gosden and Lee, 2010;Meneau et al, 2020). During the growth phase, mRNA is synthesized for either immediate translation or storage in repressive complexes (Huarte et al, 1992;Meneau et al, 2020). During the subsequent maturation phase, these repressive complexes are removed and translation is activated (Martin et al, 2019;Meneau et al, 2020;Yang et al, 2020).…”
Section: The Contribution Of Declining Proteostasis To Oocyte Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…In understanding the susceptibility of oocytes to changes in proteostasis, it is important to note that transcription ceases when oocytes complete their growth phase prior to reentry into meiosis (Gosden and Lee, 2010;Meneau et al, 2020). During the growth phase, mRNA is synthesized for either immediate translation or storage in repressive complexes (Huarte et al, 1992;Meneau et al, 2020). During the subsequent maturation phase, these repressive complexes are removed and translation is activated (Martin et al, 2019;Meneau et al, 2020;Yang et al, 2020).…”
Section: The Contribution Of Declining Proteostasis To Oocyte Agingmentioning
confidence: 99%
“…During the growth phase, mRNA is synthesized for either immediate translation or storage in repressive complexes (Huarte et al, 1992;Meneau et al, 2020). During the subsequent maturation phase, these repressive complexes are removed and translation is activated (Martin et al, 2019;Meneau et al, 2020;Yang et al, 2020). At this stage the oocyte is one of the most translationally active cells in the body, placing unique pressure on both ribosome biogenesis and accurate protein synthesis to attain competence for fertilization (Gosden and Lee, 2010;Duncan et al, 2017).…”
Section: The Contribution Of Declining Proteostasis To Oocyte Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the Gwl/ARP19/PP2A-B55 pathway acts as a major component of MPF auto-amplification, that contributes to upregulation of MPF activity ( Hara et al, 2012 ; Dupre et al, 2013 ). Notably, transcriptome-wide analysis demonstrated that massive deadenylation and degradation of mRNA occurs in Xenopus eggs at meiosis II ( Meneau et al, 2020 ; Yang et al, 2020 ). It was found that a significant fraction of egg transcripts contained, in addition to CPEs, (A + U)-rich elements (ARE), characteristic of the mRNAs regulated by deadenylation, and suggested that opposing activities of CPEs and AREs define the fate of egg mRNAs ( Belloc and Méndez, 2008 ).…”
Section: Maturationmentioning
confidence: 99%
“…Gametes are generated through the two successive meiotic cell divisions, meiosis I and meiosis II. In oocytes, meiosis is arrested at the prophase of meiosis I, and more than ten thousand mRNAs are accumulated for oocyte growth and for the progression of meiosis and embryonic development (Conti and Franciosi, 2018;Masui and Clarke, 1979;Meneau et al, 2020;Winata and Korzh, 2018). Fully grown germinal vesicle (GV)-stage oocytes resume meiosis in response to hormonal stimulation.…”
Section: Introductionmentioning
confidence: 99%